Biologics in the management of psoriasis - Jennifer D Bahner; Lauren Y Cao; Neil J Korman (Dove Medical Press, 2009)
Jennifer D Bahner1, Lauren Y Cao2, Neil J Korman11Department of Dermatology, University Hospitals Case Medical Center, Cleveland, Ohio, USA; 2Case Western Reserve University School of Medicine, Cleveland, Ohio, USAAbstract: Psoriasis is a chronic inflammatory systemic disease for which there exist topical, ultraviolet, systemic, and biologic treatments. Biologic agents selectively interfere with the immune mechanisms responsible for psoriasis. Etanercept, infliximab, and adalimumab target tumor necrosis factor-alpha and have demonstrated efficacy in the treatment of psoriasis and psoriatic arthritis. Alefacept and efalizumab target T lymphocytes, are effective in the treatment of psoriasis, but are not approved for psoriatic arthritis. Finally, ustekinumab and ABT-874 target interleukin-12 and interleukin-23, and they have demonstrated efficacy in the treatment of psoriasis. The objective of this review is to present efficacy and safety data from randomized controlled trials of the biologic agents in the treatment of psoriasis.Keywords: biologics, psoriasis, tumor necrosis factor, interleukin-12/23